2018
DOI: 10.18203/2349-3291.ijcp20181026
|View full text |Cite
|
Sign up to set email alerts
|

Henoch-Schonlein Purpura in childhood: a tertiary care hospital experience in Turkey

Abstract: Background: This study examines the clinical and laboratory features of children with Henoch-Schönlein purpura.Methods: A retrospective study was applied for the 32 Henoch-Schönlein purpura patients who were monitored between January 2014 and June 2017 at the Pediatric clinic of a tertiary care hospital. The diagnoses were made based on the HSP criteria of the American College of Rheumatology. Age, gender, clinical and laboratory findings of the patients were recorded.Results: The mean age of the 32 Henoch-Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previous studies have applied mycophenolate mofetil to the treatment of HSP children; however, the researches did not differentiate children with RT from those free of RT. Practice has shown that mycophenolate mofetil can trigger adverse reactions, and Bukulmez et al have claimed that the adverse reactions are closely related to the application dose (7). Therefore children can be classified with or without RT, and lowdose mycophenolate mofetil can be applied to children without renal trauma to reduce the incidence of adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have applied mycophenolate mofetil to the treatment of HSP children; however, the researches did not differentiate children with RT from those free of RT. Practice has shown that mycophenolate mofetil can trigger adverse reactions, and Bukulmez et al have claimed that the adverse reactions are closely related to the application dose (7). Therefore children can be classified with or without RT, and lowdose mycophenolate mofetil can be applied to children without renal trauma to reduce the incidence of adverse reactions.…”
Section: Introductionmentioning
confidence: 99%